2012
DOI: 10.1007/s10499-012-9597-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different commercial spawning agents and thermal regime on the effectiveness of pikeperch, Sander lucioperca (L.), reproduction under controlled conditions

Abstract: Pikeperch, Sander lucioperca (L.), has been identified as one of the most perspective candidates for diversification of freshwater aquaculture. However, some aspects of production are still being developed, and controlled reproduction is one of the bottlenecks. The aim of the present study was to compare the effectiveness of different commercial spawning agents in the induction of final oocyte maturation (FOM) and ovulation in wild spawners. Within the study, four spawning agents [human chorionic gonadotropin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…Generally, these authors found decreased reproductive performance in virgin breeders, compared to older spawners. The indicators of reproductive success for wild breeders in the present study were low when compared to the results of previous studies (Zakęś & Demska‐Zakęś ; Żarski, Targońska, Kaszubowski, Kestemont, Fontaine, Krejszeff, Kupren & Kucharczyk ). This could be explained by the fact that the females used in this study were small and young, factors which are assumed to result in lower spawning success (Lappalainen, Dörner & Wysujack ; Kamler ).…”
Section: Discussioncontrasting
confidence: 95%
“…Generally, these authors found decreased reproductive performance in virgin breeders, compared to older spawners. The indicators of reproductive success for wild breeders in the present study were low when compared to the results of previous studies (Zakęś & Demska‐Zakęś ; Żarski, Targońska, Kaszubowski, Kestemont, Fontaine, Krejszeff, Kupren & Kucharczyk ). This could be explained by the fact that the females used in this study were small and young, factors which are assumed to result in lower spawning success (Lappalainen, Dörner & Wysujack ; Kamler ).…”
Section: Discussioncontrasting
confidence: 95%
“…The results presented in this study did not confirm improved efficiency upon repeated sGnRHa administration, as has been reported for other freshwater non-salmonid teleosts (Kucharczyk et al, 2008). For pikeperch, repeated administration was previously tested with hCG (Zakęś et al, 2013), acetone-dried carp pituitary homogenate (Rónyai, 2007) or a mammalian GnRH analogue administered alone or together with dopamine antagonists (Křišt'an et al, 2013;Żarski et al, 2013). The results following application of those repeated injections had either negative or no effect (see Żarski et al, 2015).…”
Section: Discussionmentioning
confidence: 43%
“…However, huge intragroup variability in spawning effectiveness indicates an urgent need for additional studies that allow identification of the factors that condition egg quality, including 'time of response to the hormone' as a specific variable to be tested. Additionally, the testing of other spawning protocols, such as alternative thermal protocols, including lower and/or changeable temperature (since temperature is an important modulatory factor for FOM; Pourhosein Sarameh et al, 2012;Żarski et al, 2013) that allow control over oocyte maturation speed and, presumably, egg quality, is recommended for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, natural gonadotropins (e.g. hCG) are particularly recommended to enhance reproduction in the Percidae family (Żarski, Horváth, Kotrik, Targońska, Palińska, Krejszeff, Bokor, Urbányi & Kucharczyk ; Żarski, Targońska, Kaszubowski, Kestemont, Fontaine, Krejszeff, Kupren & Kucharczyk ; Targońska, Szczerbowski, Żarski, Łuczyński, Szkudlarek, Gomułka & Kucharczyk ). It should be stressed that hCG has also been successfully applied in the reproduction of some other multiple–spawner fish including rudd ( Scardinius erythrophthalamus ) (Kucharczyk, Kujawa, Mamcarz & Wyszomirska ) and chub ( Leuciscus cephalus ) (Krejszeff, Targońska, Żarski & Kucharczyk ).…”
Section: Discussionmentioning
confidence: 99%